Is there a choice when a sibling is ill? Experiences of children and adolescents who donated stem cells to a sibling. (June 2022) - Rinaldo, Carina; Stenmarker, Margaretha; Frost, Britt-Marie; Øra, Ingrid; Pergert, Pernilla
Abstract: Purpose: When healthy children/adolescents are potential stem cell donors to a sibling, ethical questions arise due to reduced autonomy and dependency on their family. This study aimed to explore the experiences of children/adolescents in Sweden who donated stem cells to a severely ill sibling. Method: Semi-structured interviews were conducted with thirteen donors, aged 6–17 years at the time of the donation, all with surviving siblings. The interviews were transcribed verbatim and analysed using qualitative content analysis. Result: The main category in this study was The presumed 'choice' when a sibling is ill . The experience included being Proud without an actual choice, highlights that the donors were proud to contribute, and perceptions of a request without a choice. Focusing on the ill sibling and the outcomes reveals that they were worried and protected the sibling, and downplayed the importance of their own effort. They experienced a Need of support and information, which derived from receiving information without communication about what they really needed to know, but also the importance of support through play and talk. Conclusion: The donation involves the young donor in the care, implying an opportunity to bring the family back together. They have no real choice, when their sibling is ill and the lack of information about possible alternatives indicate that there was no option to decline. There is also a need to focus on the experiences of young donors whose siblings died after the transplantation. Highlights: Paediatric donors are proud to contribute to their sibling's recovery. Paediatric donors had no choice because of the sibling's life-threatening illness. Paediatric donors need age-appropriate information through discussions and play. Despite good information the donors were worried and did not know what would happen. Few paediatric donors had discussed the consequences if the transplant would fail.